Application of cyclodextrins in chiral capillary electrophoresis. Issue 19 (10th July 2014) - Řezanka, Pavel; Navrátilová, Klára; Řezanka, Michal; Král, Vladimír; Sýkora, David; Chankvetadze, Bezhan
<x xml:space="preserve">Abstract</x> CE represents a very powerful separation tool in the area of chiral separations. CD‐mediated chiral CE is a continuously flourishing technique within the frame of the electromigration methods. In this review, a brief overview of the synthetic procedures leading to modified CDs is provided first. Next, selected aspects related to the utilization of CDs in chiral CE are discussed specifically in the view of recently published data. Advantages of CDs and basic principles of chiral CE are remained. The topic of the determination of binding constants is touched. Particular attention is paid to the effort aiming at better understanding of the molecular level of the enantiorecognition between CDs and the analyte in the solution. Powerful approaches extensively utilized in this field are NMR, molecular modeling, and computer simulations. Then, a summary of applications of CDs in the CE enantioseparations is given, covering years 2008–2013. Finally, the general trend of modified CDs use in separation science is statistically evaluated.